Sensitized Two‐NIR‐Photon Z→E Isomerization of a Visible‐Light‐Addressable Bistable Azobenzene Derivative. Issue 4 (17th December 2015) - Moreno, Javier; Gerecke, Mario; Grubert, Lutz; Kovalenko, Sergey A.; Hecht, Stefan
Abstract: Two‐NIR‐photon‐triggered Z → E isomerization of an azobenzene was accomplished by covalently linking a two‐photon‐harvesting triarylamine antenna to a thermally stable ortho ‐fluorinated azobenzene derivative. The obtained photoswitch is fully addressable with visible and NIR light by using one‐photon and two‐photon excitation, respectively, with the latter offering enhanced penetration depth and improved spatial resolution. Abstract : Red light, green light : Photoswitching with two NIR photons was accomplished by covalently linking a two‐photon‐harvesting triarylamine antenna (TPA) to a thermally stable azobenzene derivative. The new photoswitch is addressable with visible and NIR light through one‐photon and two‐photon excitation, respectively.